The Effect of Product Differentiation and Brand Image on Purchasing Decisions - Nani, N.; Halim, Agus; Inzani S.L, J Fuji Inzani SL (Golden Ratio of Marketing and Applied Psychology of Business, 2024)
This study aims to determine the effect of Product Differentiation and Brand Image variables on Purchasing Decisions for New Honda Scoopy Motorbikes at PT. Nusantara Surya Sakti Mamuju Branch, Indonesia. The research method used quantitative methods with primary data using a questionnaire. Respondents in the study were all customers who purchased a New Honda Scoopy motorcycle at PT. Nusantara Surya Sakti Mamuju Branch, Indonesia, West Sulawesi; the sample used was an accidental sampling technique with a sample size of 30 respondents. The formula in this study uses multiple linear regression, validity test, reliability test, multiple linear regression, t-test, and F test. The results in this study indicate that product differentiation and brand image have a positive and significant partial effect on purchasing decisions for New Honda Scoopy Motorbikes at PT. Nusantara Surya Sakti Mamuju Branch, Indonesia. Product differentiation and brand image significantly affect purchasing decisions for New Honda Scoopy Motorbikes at PT. Nusantara Surya Sakti Mamuju Branch, Indonesia.